PREDIKSI FINANCIAL DISTRESS PERUSAHAAN MANUFAKTUR DI INDONESIA - Muhammad Arif Hidayat; Wahyu Meiranto (Diponegoro Journal of Accounting, 2014)
This study aimed to investigate the effect of financial ratios to predict probability of financial distress in the company. Financial ratios in this study using the indicators leverage ratio, liquidity ratio, activity ratio, and profitability ratio. The population in this study are all of the companies listed on the Indonesian Stock Exchange and continuously published financial statements in the year 2008-2012. Based on purposive sampling method, samples obtained are 59 companies in the period 2008-2012, so obtain 295 observations. As for the criteria of financial distress in this study was measured by using interest coverage ratio, whilst statistic analysis that used in this study was logistic regression. The result of this research showed that leverage ratio (debt ratio), liquidity ratio (current ratio), and activity ratio (total asset turnover ratio) were financial ratios that have significant value to predict financial distress in the company, whilst profitability ratio (return on asset) is only financial ratios which not significant to predict financial distress in the company.